Analisis Variabel DPK, CAR, NPL, LDR, ROA, GWM, dan Inflasi Terhadap Penyaluran Kredit Investasi Pada Bank BUMN (Periode 2005 – 2013) - Ismaulandy, Willdan (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims  to  determine the effect of  third-party  funds  (DPK), capital adequacy ratio (CAR), loan deposit ratio (LDR), return on assets (ROA),  non-performing loan  (NPL),  reserve requirement, and inflation on investment loans in the State-Owned Enterprises Banks period 2005-2013. This research quantitative data used are secondary data and quarterly. Method of regression analysis using  panel regression.  Research  results  showed  that simultaneous  DPK,  CAR, LDR, ROA,  NPL, GWM, and inflation  has  a significant effect on  the variable  investment loans.  In parisal  investment loans  significantly affected  by  DPK  (+), CAR (+), LDR(+), and  NPL (+).Whereas ROA(+), reserve requirement (-), and inflation (-) has no significant effect on investment loans State-Owned Enterprises Banks.The rate coefficient of determination (  ) for the variables  that affect  working capital loans  amounted to  94%, which means  the independent variables  in the model is  able to explain  the dependent variable  (investment loans)  at 94%,  the remaining 6% is explained by variables outside this model.Keywords : Credit, Deposit, CAR, LDR, ROA, NPL, GWM, Inflation